The politics of fossil fuel subsidies and their reform - Skovgaard-Petersen, Jakob; Asselt, Harro van (Harro Dirk), 1979- (Cambridge : Cambridge University Press, 2018)
Fossil fuel subsidies strain public budgets, and contribute to climate change and local air pollution. Despite widespread agreement among experts about the benefits of reforming fossil fuel subsidies, repeated international commitments to eliminate them, and valiant efforts by some countries to reform them, they continue to persist. This book helps explain this conundrum, by exploring the politics of fossil fuel subsidies and their reform. Bringing together scholars and practitioners, the book offers new case studies both from countries that have undertaken subsidy reform, and those that have yet to do so. It explores the roles of various intergovernmental and non-governmental institutions in promoting fossil fuel subsidy reform at the international level, as well as conceptual aspects of fossil fuel subsidies. This is essential reading for researchers and practitioners, and students of political science, international relations, law, public policy, and environmental studies. This title is also available as Open Access.
Defining and measuring fossil fuel subsidies / Doug Koplow -- Reforming fossil fuel subsidies: the art of the possible / Shelagh Whitley and Laurie van der Burg -- The political economy of incumbency: fossil fuel subsidies in global and historical context / Peter Newell and Phil Johnstone -- Fossil fuel subsidy reform: an international norm perspective / Thijs Van de Graaf and Mathieu Blondeel -- International push, domestic reform? The influence of international economic institutions on fossil fuel subsidy reform / Jakob Skovgaard -- Fossil fuel subsidies and the global trade regime / Ronald Steenblik, Jehan Sauvage and Christina Timiliotis -- Fossil fuel subsidies and the global climate regime / Harro van Asselt, Laura Merrill and Kati Kulovesi -- Anatomy of an international norm entrepreneur: the friends of fossil fuel subsidy reform / Vernon Rive -- The global subsidies initiative: catalytic actors and the politics of fossil fuel subsidy reform / Nathan Lemphers, Steven Bernstein and Matthew Hoffmann -- Fossil fuel subsidy reform in Indonesia: the struggle for successful reform / Kathryn Chelminski -- Lessons from the world's largest subsidy benefit transfer scheme: the case of liquefied petroleum gas subsidy reform in India / Abhishek Jain, Shalu Agrawal and Karthik Ganesan -- Sustaining carbon lock-in: fossil fuel subsidies in South Africa / Jesse Burton, Tawney Lott and Britta Rennkamp -- The politics of subsidies to coal extraction in Colombia / Claudia Strambo, Ana Carolina Gonzalez Espinosa, Angelica Puertas Velasco and Aaron Atteridge -- Reforming Egypt's fossil fuel subsidies in the context of a changing social contract / Tom S. H. Moerenhout -- Actors, frames and contexts in fossil fuel subsidy reform: the case of Trinidad and Tobago / Michelle Scobie.
Title from publisher's bibliographic system (viewed on 17 Jan 2019).
Open Access title.
Keywords: Energy policy -- Economic aspects; Energy industries -- Subsidies; Fossil fuels -- Government policy